2007
DOI: 10.1093/intimm/dxm032
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule microscopy reveals heterogeneous dynamics of lipid raft components upon TCR engagement

Abstract: The existence of lipid rafts and their importance for immunoreceptor signaling is highly debated. By non-invasive single molecule imaging, we analyzed the dynamics of the T-cell antigen receptor (TCR), the lipid raft-associated glycosylphosphatidylinositol (GPI) proteins CD48 and CD59 and the major leukocyte phosphatase CD45 in living naive T lymphocytes. TCR triggering induced the immobilization of CD45 and CD48 at different positions within the T-cell interface. The second GPI protein, CD59, did not co-immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 49 publications
(70 reference statements)
4
30
0
Order By: Relevance
“…Previous work has examined the diffusion of CD45 by FPR (15), and experiments with activated cells are in agreement with our observations of reduced lateral mobility (17). CD45 receptors lacking a cytoplasmic domain have been reported to have much higher diffusion coefficients than observed in our experiments, implicating the cytoplasmic domain in the regulation of mobility (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous work has examined the diffusion of CD45 by FPR (15), and experiments with activated cells are in agreement with our observations of reduced lateral mobility (17). CD45 receptors lacking a cytoplasmic domain have been reported to have much higher diffusion coefficients than observed in our experiments, implicating the cytoplasmic domain in the regulation of mobility (16).…”
Section: Discussionsupporting
confidence: 92%
“…Single-particle tracking (SPT) experiments on CD45 with a cytoplasmic domain deletion showed rapid diffusion that was unaffected by cellular activation (16). SPT measurements on CD45 with an intact cytoplasmic domain revealed a significant decrease in mobility upon cellular activation, suggesting increased cytoskeletal interactions (17). Thus, the lymphocyte cytoskeleton plays an active role in CD45 regulation and lateral mobility.…”
mentioning
confidence: 92%
“…We found that T cell stimulation on planar CD3 mAb coated surfaces induced the immobilization of CD48 in the center of the T cell interface whereas the second GPI protein, CD59, remained highly mobile (14). Heterogeneity in the behavior of lipid raft molecules and different lipid composition of microdomains has been already demonstrated by others (15)(16)(17), however, it is still not clear what molecular interactions determine this diversity.…”
mentioning
confidence: 69%
“…To elucidate further the significance of CD48 colocalization with 2B4, we performed solid-phase signalosome precipitation for the receptor complex. Using a procedure that does not solubilize the raft, it was possible to visualize components in the detergent-insoluble raft complex (16). As shown in Fig.…”
Section: Coclustering Of Cd48 With 2b4mentioning
confidence: 99%